Sistem Pendukung Keputusan Karyawan Berprestasi Menggunakan Metode Analytical Hierarchy Process (AHP) Pada PT. Intisel Prodaktifakom Semarang - Wakhidah, Nur; Santoso, Bayu Adi (Jurnal Pengembangan Rekayasa dan Teknologi, 2020)
Analitical Hierarchy Process method is a relative measurement method that can use subjective and intangible criteria. AHP also has a consistency measurement mechanism. Therefore the research developed software with AHP method that can be used by PT. Intisel Prodaktifakom to assist the decision-making process in determining employee achievement. AHP stages such as determining criteria, determining alternatives, making pairwise comparisons, calculating consistency index values, calculating consistency ratios calculating criteria values, calculating alternative values, determining alternative ranking, and producing reports / decisions included as software features. Software development using prototype process models, system modeling is done using UML, and implementation / coding is done using the PHP programming language. It is hoped that the results of this research software can make it easier for PT. Intisel Prodaktifakom in determining employee achievement